Stratégies musicales de préservation et d'adaptation chez les Urainiens-Montréalais - Berthiaume-Zavada, Claudette (MUSICultures, 1989)

Judeo-Spanish Song in the Sephardic Communities of Montreal and Toronto - Cohen, Judith R. (Université de Montréal, 1989)

"Ya salio de la mar": Judeo-Spanish Wedding Songs among Moroccan Jews in Canada - Cohen, Judith R. (Women and Music in Cross-Cultural Perspective, 1989)

Music and gender in the sub-arctic Algonkian area - Diamond, Beverley (Women in North American I[*****] Music: Six Essays, 1989)

Le plain-chant chez les Amérindiens - Dubois, Paul-André (Grégoriana, 1989)
Keywords: Pas de lien web

Maureen Forrester. Au-delà du personnage. Un récit autobiographique - Forrester, Maureen; McDonald, Marci (Éditions Libre Expression, 1989)
Les petits et grands moments de la vie et de la carrière de l'artiste.
Google-Books-ID: QjWtcQAACAAJ

Who's Who of Jazz in Montreal: Ragtime to 1970 - Gilmore, John (Véhicule Press, 1989)

Les Ursulines et la musique - Gréroire-Reid, Claire; V. -Demers, Micheline (Cap-aux-Diamants : la revue d'histoire du Québec, 1989)
Publisher: Les Éditions Cap-aux-Diamants inc.

Népal. L'échappée belle - Julien, Pauline; Hébert, Denise (VLB Éditeur, 1989)

Analyse de la composition musicale Coulage - Pelletier, Marie (Université de Montréal, 1989)
Keywords: Pas de lien web

La pratique de la musique liturgique et paraliturgique des Juifs originaires du Maroc à Montréal - Sabbah, Dina (Université de Montréal, 1989)

Histoire des femmes auteures-compositeures dans la chanson canadienne-française, 1730-1985 - Tremblay-Matte, Cécile (Université de Montréal, 1989)

Petite histoire des musiques afro-montréalaises - Villefranche, Robert; Bernard, Yves (MUSICultures, 1989)
Robert Villefranche and Yves Bernard describe the history of Montreal musicians of African descent, telling of the formation of various groups that performed at community events and festivals and became more widely known through recordings and festivals.